An investigation of the aging of electro exploded platinum nanopowder - Chen, Wei. (2012)
Aged wire electro-exploded, platinum nanopowder has been characterized by differential scanning calorimetry (DSC) and a comparative analysis made between virgin and aged platinum nanopowder. The platinum nanopowder had a wide distribution of particle sizes between 5 to 250 nm and a purity of 99.9%. The powder was highly agglomerated, with a high density of defects. For virgin platinum nanopowder, the differential scanning calorimetry (DSC) results indicated that there are two endothermic reactions at about 100°C and 350°C, an exothermic reaction within the temperature range of 173.4°C to 198.57°C. The two reaction peaks are likely due to melting and crystallization. The activation energy of the virgin platinum was about 96±5% KJ/mol for exothermic peak. The DSC indicated that the peak temperature of exothermic peak for aged Platinum nanopowder appeared to be shifted up by 2% when it was pre-sintered at 100°C for up to five hours. When it was aged for eight hours, the peak temperature was increased by 4% compared to normal powder. According to the finding, the calculated activation energy for age platinum nanopowder was 97KJ/mol. It was no difference comparing with virgin platinum nanopowder.